Pengajaran Bahasa Inggris Menggunakan Media Audio Visual di Raudhatul Atfal (RA) Dharma Wanita Persatuan Simpang - Muklas, M; Agustina, Eka; Andriani, Dwi (Jurnal Indonesia Mengabdi, 2019)
This Community Service aims to provide assistance in learning English about pronunciation of vocabulary using Audio Visual and providing knowledge about the use of Audio Visual media for teachers and learning for students. The chosen partners in this service are children an teachers of Raudhatul Atfal (RA) Dharma Wanita eersatuan Simpang, Buay Pemaca, OKU Selatan, with the consideration that they rarely learn English because there is no English teacher in the RA in using learning methods. In addition, based on observations in the RA, it shows that children's lack of interest in learning English and even English for them is too ordinary / foreign. The target in this service is to help the children of RA Dharma Wanita Persatuan Simpang to learn English so that they do not feel unfamiliar / unfamiliar and increase student motivation in learning English and minimize errors in speaking vocabulary in English. From the results of this service activity, it can be concluded that learning English by utilizing audio-visual media in students of RA Dharma Wanita Persatuan Simpang is proven to contribute significantly to the mastery of the English vocabulary of students.